1995
DOI: 10.1038/378182a0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct components of spatial learning revealed by prior training and NMDA receptor blockade

Abstract: Synaptic plasticity dependent on N-methyl-D-aspartate (NMDA) receptors is thought to underlie certain types of learning and memory. In support of this, both hippocampal long-term potentiation and spatial learning in a watermaze are impaired by blocking NMDA receptors with a selective antagonist D(-)-2-amino-5-phosphonovaleric acid (AP5) or by a mutation in one of the receptor subunits. Here we report, however, that the AP5-induced learning deficit can be almost completely prevented if rats are pretrained in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
385
7
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(425 citation statements)
references
References 22 publications
29
385
7
4
Order By: Relevance
“…Perceptual learning, which can refer to a learned change in the salience and discriminability of a stimulus, is a well-documented and widespread consequence of stimulus exposure, and it profoundly alters how a subject learns about the CS during subsequent conditioning (Hall, 1991). These results are consistent with studies from spatial learning (Bannerman et al, 1995;Saucier & Cain, 1995;Saucier et al, 1996), Pavlovian contextual fear conditioning (Sanders & Fanselow, 2003) and one-trial inhibitory avoidance learning (Roesler et al, 1998), showing that the preexposure to the stimuli or actions to be learned about can determine the effects of NMDA receptor antagonism on later learning. In the case of fear extinction, the present results raise the question: What aspect of fearextinction learning do NMDA receptor antagonists normally disrupt?…”
Section: Discussionsupporting
confidence: 80%
“…Perceptual learning, which can refer to a learned change in the salience and discriminability of a stimulus, is a well-documented and widespread consequence of stimulus exposure, and it profoundly alters how a subject learns about the CS during subsequent conditioning (Hall, 1991). These results are consistent with studies from spatial learning (Bannerman et al, 1995;Saucier & Cain, 1995;Saucier et al, 1996), Pavlovian contextual fear conditioning (Sanders & Fanselow, 2003) and one-trial inhibitory avoidance learning (Roesler et al, 1998), showing that the preexposure to the stimuli or actions to be learned about can determine the effects of NMDA receptor antagonism on later learning. In the case of fear extinction, the present results raise the question: What aspect of fearextinction learning do NMDA receptor antagonists normally disrupt?…”
Section: Discussionsupporting
confidence: 80%
“…Prior experience in a water bath has been shown to a¡ect subsequent learning performance in males (e.g. Bannerman et al 1995) and Perrot-Sinal et al (1996a) found that prior training in a water maze improved the performance of both males and females but eliminated the male advantage. Perrot-Sinal et al's (1996a) explanation for this result was that the sex di¡erences seen in maze performance might be due to the di¡erential e¡ects of stress on males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Although hippocampal LTP and spatial learning are impaired by NMDA receptor blockade 270 , learning deficits can be almost completely prevented if rats are previously trained in a different water maze 301,302 . Therefore, NMDA receptors may not be required for encoding the spatial representation of a specific environment but rather in other forms of memory important for learning this task 303 .…”
Section: ) Synaptic Plasticitymentioning
confidence: 99%